2016
DOI: 10.1016/j.jcat.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum carbide nanoparticles as a catalyst for the hydrogen evolution reaction and the effect of pH

Abstract: 11Molybdenum carbide nanoparticles supported on carbon catalysts have been prepared 12 with a modified carbothermal reduction method. The soft carburization conditions of 13 this method allows the preparation of a nanoparticulate Mo2C even with high Mo 14 loading (50 wt%). The catalytic activity towards hydrogen evolution reaction was 15 analyzed both in an electrochemical cell at various pHs and in a laboratory-scale 16 electrolyser. These nanoparticles were found to be very active for catalyzing hydrogen 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…A Tafel plot of the catalyst reveals the rate‐limiting step in HER. Tafel slopes of 120, 40, 30 mV dec −1 correspond to the rate‐determing step of Volmer, Heyrovsky and Tafel reactions, respectively . Thus, the Tafel slope can be adopted as a guide to identify the HER mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…A Tafel plot of the catalyst reveals the rate‐limiting step in HER. Tafel slopes of 120, 40, 30 mV dec −1 correspond to the rate‐determing step of Volmer, Heyrovsky and Tafel reactions, respectively . Thus, the Tafel slope can be adopted as a guide to identify the HER mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…[25] Meanwhile, researches have also shown that the measurement conditions including electrolytes with various pH values and temperatures as well as catalyst loading play important roles in affecting the current densities and Ta fel slopes toward HER. [26] As an important member of TMCs, Mo x Cw ere initially applied as catalysts to reactions such as alkanei somerization, [27,28] hydrogenation, [29] hydrodesulfurization and denitrification. [30,31] Mo x Ci tself is an extremelyh ard refractory ceramic material with an inherent bulk structure.…”
Section: Her and Molybdenum Carbidesmentioning
confidence: 99%
“…[75] At ypical example is carbon black (CB), which shows as uperior HER activity to unsupported Mo 2 C electrocatalyst. [26] Carbon nanotubes (CNTs) and carbon xerogel (CXG) are also reported to load Mo 2 C. [76] Compared to CB, onedimensional CNTs-supportedM o x Ce xhibit ab etter electrochemicalp erformance (Figure 5a-c), which is attributed to af aster kinetics that is characterized by al ower charge-transfer impedance of 21 W cm 2 of Mo 2 C/CNTs( vs. 36.1 W cm 2 of Mo 2 C/ CB). [77] However,M o 2 C/CNTsc atalyst exhibits al ower activity than Mo 2 C/CXG at mosto ft he potential ranges measured.…”
Section: Mo X Cn Anoparticlesmentioning
confidence: 99%
“…[38] It is generallya ccepted that hydrogen evolution in acidic condition consists of two steps. [39] In Figure 5b,t he Tafel slope of Pt/C is 30 mV dec À1 ,c orresponding to aT afel mechanism. [8] Al ower Ta fel slope value of 82 mV dec À1 is obtained for MoC x /Ni-650, which suggests am ixed Volmer-Heyrovsky mechanism for HER.…”
Section: Resultsmentioning
confidence: 85%
“…The first is a proton adsorption with charge transfer step (Volmer reaction): H 3 O + +e − →H ads +H 2 O, while the second is a desorption step (Heyrovsky reaction): H ads +H 3 O + +e − →H 2 +H 2 O, or a recombination step (Tafel reaction): H ads +H ads →H 2 , where H ads represents H atoms adsorbed on the active sites of the catalyst. According to the kinetic model, Tafel slopes of 120, 40, 30 mV dec −1 correspond to the rate‐determining steps of Volmer, Heyrovsky and Tafel reactions, respectively . In Figure b, the Tafel slope of Pt/C is 30 mV dec −1 , corresponding to a Tafel mechanism .…”
Section: Resultsmentioning
confidence: 97%